1997
DOI: 10.1021/ac9706077
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch-Sensitive Hybridization Detection by Peptide Nucleic Acids Immobilized on a Quartz Crystal Microbalance

Abstract: A quartz crystal microbalance DNA hybridization biosensor, based on thiol-derivatized peptide nucleic acid (PNA) probes, offers unusual in situ differentiation of single-base mismatches. A large excess of a single-base mismatch oligonucleotide has no effect on the frequency response of the target. Such remarkable distinction between perfect matches and mismatches is illustrated by the detection of a common mutation in the p53 gene. The greater specificity of the new mass-sensitive indicatorless hybridization d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
88
0
4

Year Published

1999
1999
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(96 citation statements)
references
References 16 publications
4
88
0
4
Order By: Relevance
“…16 The nanopores were prepared by electroless Au plating of track etch polycarbonate membranes. 10 In order to obtain regular pore diameters and better control of the plating process, the original recipe was slightly modified in that the membranes were dried in N 2 atmosphere before placing them in the Au plating solution of pH 10 kept at 1 °C.…”
mentioning
confidence: 99%
“…16 The nanopores were prepared by electroless Au plating of track etch polycarbonate membranes. 10 In order to obtain regular pore diameters and better control of the plating process, the original recipe was slightly modified in that the membranes were dried in N 2 atmosphere before placing them in the Au plating solution of pH 10 kept at 1 °C.…”
mentioning
confidence: 99%
“…They are easily manufactured and modified and have good hybridization properties compared with DNA oligos. PNA has been used in a handful of SNP genotyping assays (13)(14)(15)(16)(17)(18)(19) and as RNA capture probe coupled to the surface of microspheres (25).…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that short PNA beacons can successfully replace DNA-based probes in two real-time polymerase chain reaction (PCR) genotyping assays (13). Other groups have reported PNA-based allele discrimination using mass spectroscopy (14 -16), quartz crystal microbalance biosensors (17), surface plasmon resonance (18), or fluorescence polarization (19).…”
mentioning
confidence: 99%
“…PNA was developed [1] as a new oligomer having high affinity hybridization with single-strand DNA. PNA is a nucleic acid analogue of DNA, in which the phosphate backbone of DNA is replaced with a structurally homomorphous pseudopeptide backbone.…”
Section: Introductionmentioning
confidence: 99%